Merjenje, spremljanje in ugotavljanje uspešnosti slovenskih knjižnic - Kodrič-Dačić, Eva (Knjižnica, 2014)
Statistical measurements of Slovenian libraries' activities and the tools for measuring library development and effectiveness are presented. The Library System Development Centre at the National and University Library started to develop the BibSiSt portal in 2005. The module enables interactive entry of data on libraries´ activities as well as data presentation, giving definitions and methodological explanations required to make proper interpretation of statistical data. In 2012, a new statistical module for indicators was released, facilitating simple measurement of library effectiveness on the basis of selected performance indicators. The selection of indicators was based on the ISO 11620 standard and on the generally accepted performance indicators in Slovenia as well as on related international projects. The main criterion for the selection of indicators was the quality of the obtained statistical data. On the basis of the Minimum Standard Guidelines for Public Library Service in Slovenia a methodology for libraries' measurement and formulation of opinions issued by the Library System Development Centre was developed followed by the module for measuring library development and progress. The module enables interactive data gathering and formulation of opinions. The administrator interface allows to maintain a directory of statistical units and to monitor statistical measurements.
Keywords: knjižnična statistika; library statistics; kazalci uspešnosti knjižnic; library indicators; library effectiveness; merjenje uspešnosti knjižnic